1994
DOI: 10.1200/jco.1994.12.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of enriched CD34-positive autologous marrow into breast cancer patients following high-dose chemotherapy: influence of CD34-positive peripheral-blood progenitors and growth factors on engraftment.

Abstract: CD34+ marrow and/or PBPCs provide reliable and timely hematopoietic reconstitution in breast cancer patients receiving high-dose chemotherapy. Contamination of both marrow and PBPCs with breast cancer cells was reduced using this positive selection technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
183
0
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(196 citation statements)
references
References 25 publications
12
183
0
1
Order By: Relevance
“…Although these observations certainly provide no clear-cut evidence, ex vivo purging appears to be essential in patients with CLL. In contrast to marrow grafts, PBPC collection products have the advantage that their engraftment potential is not or only slightly reduced by immunological purging (Brugger et al, 1994;Shpall et al, 1994;Dreger et al, 1995a;Straka et al, 1995). During the course of this study, our B-cell depletion procedures were steadily refined.…”
Section: Discussionmentioning
confidence: 99%
“…Although these observations certainly provide no clear-cut evidence, ex vivo purging appears to be essential in patients with CLL. In contrast to marrow grafts, PBPC collection products have the advantage that their engraftment potential is not or only slightly reduced by immunological purging (Brugger et al, 1994;Shpall et al, 1994;Dreger et al, 1995a;Straka et al, 1995). During the course of this study, our B-cell depletion procedures were steadily refined.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies showed engraftment with enriched CD34 + cell fractions, [4][5][6][7][8][9][10][11][12] but these components were only 42-73% CD34 + cells. With more highly purified CD34 + cell fractions, it is necessary to assess whether or not a required accessory cell (or cells) is depleted from the components.…”
mentioning
confidence: 99%
“…However, the major rationale for CD34-positive cell selection in autologous marrow and stem cell transplantation is a reduction or removal of contaminating tumour cells accidentally coharvested during leukapheresis to avoid their reinfusion after high-dose therapy. 19,20 In this report we compare CD34 + cell enrichment, CD34 + cell recovery, and the efficacy of purging of experimentally seeded breast cancer cells from bone marrow and G-CSF- …”
mentioning
confidence: 99%
“…However, the major rationale for CD34-positive cell selection in autologous marrow and stem cell transplantation is a reduction or removal of contaminating tumour cells accidentally coharvested during leukapheresis to avoid their reinfusion after high-dose therapy. 19,20 In this report we compare CD34 + cell enrichment, CD34 + cell recovery, and the efficacy of purging of experimentally seeded breast cancer cells from bone marrow and G-CSF-mobilised peripheral blood stem cell collections between three devices using immunoaffinity and magnetic microbeads for separation of anti-CD34 antibody-labelled CD34 + cells. We show that CD34 + enrichment leads to a decrease in the total number of contaminating tumour cells up to 4.3 log steps with reasonably high recovery of CD34-positive progenitor cells.…”
mentioning
confidence: 99%